Induction of Vertebrate Regeneration by a Transient Sodium Current - Tseng, Ai-Sun (Society for Neuroscience, 2010)
Amphibians such as frogs can restore lost organs during development, including the lens and tail. To design biomedical therapies for organ repair, it is necessary to develop a detailed understanding of natural regeneration. Recently, ion transport has been implicated as a functional regulator of regeneration. Whereas voltage-gated sodium channels play a well known and important role in propagating action potentials in excitable cells, we have identified a novel role in regeneration for the ion transport function mediated by the voltage-gated sodium channel, Na(V)1.2. A local, early increase in intracellular sodium is required for initiating regeneration following Xenopus laevis tail amputation, and molecular and pharmacological inhibition of sodium transport causes regenerative failure. Na(V)1.2 is absent under nonregenerative conditions, but misexpression of human Na(V)1.5 can rescue regeneration during these states. Remarkably, pharmacological induction of a transient sodium current is capable of restoring regeneration even after the formation of a nonregenerative wound epithelium, confirming that it is the regulation of sodium transport that is critical for regeneration. Our studies reveal a previously undetected competency window in which cells retain their intrinsic regenerative program, identify a novel endogenous role for Na(V) in regeneration, and show that modulation of sodium transport represents an exciting new approach to organ repair.